The Role of Islamic Religious Education in the Formation of Moral Character Values in the Digital Era at UPT SD Negeri 158 Mundan Enrekang Regency - Usnul Lestari; Syarifuddin Yusuf; Sumadin Sumadin; St. Nurhayati Ali; Amir Patintingan (Institut Teknologi Pendidikan Indonesia, 2026)
This article examines the role of Islamic Religious Education (PAI) in shaping students' moral character in the digital era at UPT SD Negeri 158 Mundan, Enrekang Regency. The study employed a qualitative approach with a single case study design. Data were collected through observation, in-depth interviews, and documentation, involving the principal, two PAI teachers, four class teachers, and eight students as informants. Analysis was conducted through data reduction, data presentation, and conclusion drawing, with validity tests using credibility, transferability, dependability, and confirmability. The findings indicate that: first, PAI plays a strategic role as a moral foundation by instilling values of honesty, responsibility, discipline, and courtesy through teacher exemplary behavior and religious habituation; second, moral character education is implemented in an integrated manner throughout all learning stages with a contextual approach linking moral material to digital life realities; third, major challenges include digital distraction, the gap between knowing and doing, and insufficient parental supervision; fourth, character formation results show positive development in students' moral awareness, although internalization levels vary across grade levels. The effectiveness of PAI as a moral shield in the digital era requires ongoing synergy among schools, families, and the social environment.